Determinación del tiempo de agitación y volúmen óptimo del peróxido de hidrógeno en la degradación del efluente cianurado de la planta de tratamiento de aguas de la empresa consorcio minero horizonte - López Otiniano, Carlos Joel (2018)
The purpose of this investigation was to determine the agitation time and the optimum volume of 50% H2O2 solution that the Consorcio Minero Horizonte water treatment plant requires for the efficient degradation of its cyanide effluents. By means of 4 tests with H2O2 volumes of 0.5, 1.0, 1.5 and 2.0 mL respectively, and maintaining the pH in a range between 10.5 and 11.5, in each one 1 L of cyanide effluent was treated with an average initial concentration of 130 ppm of free cyanide. The results obtained showed that the best agitation time is 225 minutes, and by means of a statistical analysis by approving anova at a confidence level of 95%, the optimal volume of H2O2 at 50% of 2.0 mL was determined, since degradation is obtained of the cyanide effluent at 85.94%; Likewise, thanks to these data, Consorcio Minero Horizonte saves US $ 0.18 per day for each cubic meter of treated cyanide effluent, which represents 9.78% less in detoxification cost per m3. Consequently, with all these details, the company Consorcio Minero Horizonte is expected to regulate its cyanidation processes, in order to optimize its business work and corroborate its commitment towards the conservation of the environment